STRATEGI MENGAJAR PENDIDIK DALAM MENGATASI KEBERAGAMAN KARAKTER DISIPLIN PESERTA DIDIK KELAS III DI SEKOLAH DASAR - Bunga Nitara, Natasya; Hariyanto; Luthvi Azizah, Alif; Sofia, Ari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teaching strategies implemented by educators in elementary schools have not yet fully addressed the diverse disciplinary characteristics of students. This study aims to describe educators’ understanding of variations in students’ disciplinary character, identify the teaching strategies employed, analyze the supporting and inhibiting factors in their implementation, and explain the impact of these strategies on the development of student discipline. The research adopts a descriptive qualitative method, with data collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing, strengthened by source and technique triangulation. The findings indicate that educators understand differences in students’ disciplinary character, as reflected in aspects such as attendance, compliance with rules, and responsibility in completing tasks, and respond to these differences by applying positive reinforcement, individual approaches, role modeling, habituation, and flexible learning methods. The effectiveness of these strategies is supported by parental cooperation and school policies, while the obstacles include differences in students’ backgrounds, uneven learning motivation, and limited time for classroom management. Overall, the implementation of adaptive and consistent teaching strategies has been shown to have a positive impact on improving student discipline, particularly in terms of rule compliance and task completion. Keywords: discipline, diversity of character, third-grade students, teaching strategies